Development and Evaluation of the INSIGHT Digital Reflective Journal for Supporting Post-Training Evaluation and Learning Transfer in Public-Sector Contexts - Kiki Kurniati; Triana Rejekiningsih; Sri Sumaryati (Journal of Education Technology, 2026)
Post-training evaluation practices in public-sector organizations remain predominantly focused on satisfaction surveys and short-term assessments, limiting their ability to capture reflective processes, behavioral change, and workplace learning transfer. This study aims to develop and evaluate the effectiveness of the INSIGHT digital reflective journal as a reflection-based evaluation instrument supporting continuous professional learning within Indonesia’s National Agency of Drug and Food Control (BPOM). A research and development (R&D) approach using the ADDIE model was employed, while mixed methods were applied to examine usability, reflective depth, and the system’s contribution to learning evaluation. Data were collected through expert validation, usability questionnaires, structured reflective journals, and interviews. Participants consisted of media experts, evaluation experts, and BPOM employees involved in training programs. Findings revealed that the INSIGHT system achieved a high feasibility level, with an average usability score of 4.59. Reflective analysis demonstrated dominant critical and transformative reflection levels, characterized by participants’ ability to formulate action plans and connect training outcomes with workplace practices. Results indicate that the digital reflective journal effectively supports learning evaluation, learning transfer, and the development of a reflective, data-informed learning culture within public-sector professional development systems.